Prevention and control strategies for the post-pandemic era: finding a balance between COVID-19 and reviving medical service - Shuang Liu; Yan Ren; Hong Li; Yue Liu; Jiao Shan; Lin Yang; Lihong Chen; Hui Chen (Journal of Infection in Developing Countries)
Introduction: Public life in China is gradually returning to normal with strong measures in coronavirus 2019 (COVID-19) control. Because of the long-term effects of COVID-19, medical institutions had to make timely adjustments to control policies and priorities to balance between COVID-19 prevention and daily medical services.